2022
DOI: 10.1093/nop/npac038
|View full text |Cite
|
Sign up to set email alerts
|

The Montreal Cognitive Assessment (MoCA) in neuro-oncology: A pilot study of feasibility and utility in telehealth and in-person clinical assessments

Abstract: Background Cognitive impairments are a common burden for patients with primary CNS tumors. Neuropsychological assessment batteries can be too lengthy, which limits their use as an objective measure of cognition during routine care. The purpose of this study was to evaluate the feasibility and utility of the brief Montreal Cognitive Assessment (MoCA) in routine in-person and telehealth visits (as a result of the global COVID-19 pandemic) with neuro-oncology patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…In addition, the results of comprehensive battery may be affected by the professional expertise and level of experience of the evaluators, limiting the scope of its application as routine tests. Therefore, researchers tried to investigate the use of MoCA in the primary brain tumor population, especially in the setting of global COVID-19 pandemic (16,42).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the results of comprehensive battery may be affected by the professional expertise and level of experience of the evaluators, limiting the scope of its application as routine tests. Therefore, researchers tried to investigate the use of MoCA in the primary brain tumor population, especially in the setting of global COVID-19 pandemic (16,42).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggested that KPS, age, education, and previous treatment were associated with patient MoCA outcomes and that the cutoff score appropriate for neuro-oncology establishment required further validation (16,40). Therefore, based on our results, MoCA administration for neurocognitive monitoring was feasible and convenient for patients undergoing awake surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore it is an imperative to reliably detect cases of cognitive impairment. Due to the high comorbidity of hearing loss and cognitive impairment ( Lin et al, 2013 ; Teipel et al, 2015 ; Fritze et al, 2016 ; Huang et al, 2023 ; Tamblay et al, 2023 ), cognitive screening has gained increasing awareness beyond geriatric or psychiatric settings ( Mordenfeld et al, 2020 ; Susano et al, 2020 ; Canavan and O’Donnell, 2022 ; Jammula et al, 2022 ; Tsui et al, 2022 ) including ENT departments and audiology ( Mosnier et al, 2018 ; Humes, 2020 ; Sanders et al, 2021 ; Völter et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%